Effectiveness Of Employee Engagement On Hotel Staff Performance - Sheta, Nadia Nara; Catur Afriasih, Maria Ulfah (Politeknik Internasional Bali, 2023)
Employee engagement is the attachment of employees to the company. Employees who are tied to actively engaged companies tend to have higher levels of productivity. There are many elements that affect employee performance, including the interaction between the workforce and the workplace environment. The objective of this study is to ascertain how employee involvement affects hotel staff's performance. The population of this study was made up of employees of the hotel, with 65 respondents. Data collection techniques using Google Form Questionnaires This research method is a descriptive analysis with a quantitative approach. The methods used are the validity test, reality test, descriptive statistical analysis, mean test, and Spearman rank correlation test. The findings indicated that the correlation of 0.969 shows a very strong relationship between the variables of employee engagement and performance. It can therefore be concluded that raising employee engagement will also raise employee performance. There is a very strong and unidirectionally significant association between staff engagement and performance at Hotel Jakarta if it can be determined that H0 is rejected and H1 is approved.